Radioactive iodine (I-131) therapy isolation rooms: Introduction of lead glass window on the wall for patient comfort and better ambience - Al Aamri, Marwa; Ravichandran, Ramamoorthy; Al Balushi, Naima (World Journal of Nuclear Medicine, 2019)
For administration of radioactive iodine for the treatment of differentiated cancer thyroid patients, activities ranging between 1.85GBq and 7.0GBq are used. The construction of concrete rooms cleared by national regulatory authorities do not recommend the presence of windows on the walls or advise same lead equivalence of wall for the lead glass if they are put on the walls. To avoid phobia of patients to give consent for I-131 treatment and to stay in isolation rooms, a necessity was felt to introduce glass window on the opposite side wall of entrance door, which had a service corridor with restricted entry, opening toward garden area. Commercially available lead glass used for X-ray computed tomography scanner was fixed on the 0.35 m thick concrete wall in two rooms. The adequacy of protection offered by the lead glass was determined. A I-131 capsule 600 MBq was moved at a distance 50 cm away from the wall inside the room, and transmitted radiation was measured outside the room. An end window pancake type, beta-gamma survey meter was used. The measured values were normalized for 3.7 GBq at 2 m bed position in μSv/h. The obtained maximum exposure rate was 1.48 μSv/h transmitted from the glass window, against 0.44 μSv/h transmitted at full concrete wall level. As the patients provide shielding to the administrated activity, also the activity is progressively decreasing fast with an effective half-life, the stray radiation levels will be decreasing outside, reducing the mean radiation level to 0.74 μSv/h, and increasing the efficacy of protection. The patient's bed position is at lower level by 0.5 m from the lower edge of the lead glass, so that during patient is in bed the stray radiation levels reduce further. As there are no reports about such facility for isolation rooms, this report may be of value in health physics literature.
Keywords: Carcinoma thyroid; I-131 isolation rooms; lead glass window; stray radiations